Towards the development of a bio-fertiliser using mixed liquor from high rate algal oxidation ponds - Masudi, Wiya Léon (Rhodes University, Faculty of Science, Institute for Environmental Biotechnology, 2020)
Mixed liquor includes consortia of microalgae and bacteria produced in high rate algal oxidation ponds (HRAOPs). The consortia of microalgae and bacteria occur as flocs called microalgae-bacterial flocs (MaB-flocs). This study aimed to source bacteria from MaB-flocs generated in HRAOPs and, after isolation and identification, evaluate their potential as plant growth promoting (PGP) microorganisms. Twelve bacterial strains namely ECCN 1b, ECCN 2b, ECCN 3b, ECCN 4b, ECCN 5b, ECCN 6b, ECCN 7b, ECCN 8b, ECCN 9b, ECCN 10b, ECCN 11b, and ECCN 12b were successfully isolated and their molecular identity established using amplified 16S rRNA gene sequence analysis that was compared to sequences deposited in the NCBI gene database. Blast analysis identified these isolates at the genus level as Bacillus strain ECCN 1b, Fictibacillus strain ECCN 2b, Bacillus strain ECCN 3b, Aeromonas strain ECCN 4b, Exiguobacterium strain ECCN 5b, Arthrobacter strain ECCN 6b, Enterobacter strain ECCN 7b, Exiguobacterium strain ECCN 8b, Microbacterium strain ECCN 9b, Pseudomonas ECCN strain 10b, Ancylobacter strain ECCN 11b and Microbacterium strain ECCN 12b. These isolates were able to grow in nutrient broth in a pH range between 6 and 10, with the best growth achieved at pH 8 to 9. The results on the use of carbon substrate revealed that 5 strains including Arthrobacter strain ECCN 6b, Aeromonas strain ECCN 4b, Pseudomonas strain ECCN 10b, Enterobacter strain ECCN 7b and Bacillus strain ECCN 3b were capable of using glucose, sucrose and mannitol. No faecal coliforms were found. However, of the 12 isolates screened for bio-fertilisation potential, Bacillus strain ECCN 1b, Fictibacillus strain ECCN 2b, Bacillus strain ECCN 3b, Aeromonas strain ECCN 4b, Exiguobacterium strain ECCN 5b, Arthrobacter strain ECCN 6b, Enterobacter ECCN strain 7b, Exiguobacterium strain ECCN 8b and Pseudomonas strain ECCN 10b showed multifunctional plant growth promoting (PGP) potential. The potential for PGP included the production of ammonium-N, solubilisation of phosphate-P and potassium-K, oxidation of Mn and production of auxin, indole-3-acetic acid (IAA). Results are discussed in terms of the amount or concentration (mg L-1) of plant essential nutrient and growth regulator produced by these isolated bacteria. Even so, further studies are needed to test and confirm the bio-fertiliser and plant growth promoting activity of these strains in pot trials and field experiments, or both.
Keywords: Biofertilizers; Microalgae - Biotechnology; Algae -- Culture